The Evidential Power of a Private Deed Legalized and Notarized by a Notary - Prasetyo Widodo Putra, Bamas; Arifulloh, Achmad; Winjaya Laksana, Andri (TABELLIUS: Journal of Law, 2026)
A private deed is a legal document created and signed by the parties without the direct involvement of a public official, such as a notary. However, in practice, private deeds can be strengthened through legalization or waarmerking by a notary. This study aims to analyze the legal force of private deeds after legalization and waarmerking, as well as the differences between them and authentic deeds. The research method used is normative juridical with a statutory approach and case studies. The results show that legalization provides additional evidentiary strength for the signature and date of the deed, making the deed a stronger evidence in legal proceedings. Meanwhile, waarmerking only records the date the deed was submitted to the notary, without guaranteeing the accuracy of its contents. Both do not change the status of the deed to an authentic deed, but they have important value in civil evidence. Therefore, the choice between legalization and waarmerking must be adjusted to the legal needs of the parties.